2018
DOI: 10.4103/ija.ija_230_18
|View full text |Cite
|
Sign up to set email alerts
|

Combination of lumbar erector spinae plane block and transmuscular quadratus lumborum block for surgical anaesthesia in hemiarthroplasty for femoral neck fracture

Abstract: Femur neck fractures may occur in elderly patients with multiple co-morbidities. Spinal or general anaesthesia may not be safe in such patients, leading to a search for other safer alternatives. Herein, we report a case in which a never previously reported combination of quadratus lumborum block (QLB) and erector spinae plane block (ESPB) was successfully used as the main anaesthetic method for hemiarthroplasty. An 86-year-old female patient with severe aortic stenosis was scheduled for internal fixation or he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
1
25
1
Order By: Relevance
“…Only a few case reports have reported sensorial findings after lumbar ESPB. 8,17,23,25,28,30,[35][36][37][38][39][40][41][42][43][44][45][46][47] Spread of LA between T12 and S1 dermatomes were reported when 30-40 mL of LA was used, 28 with similar findings for the lower volume of 20 mL also reported. 30,38 Low volume injections have generally been utilized in back pain and spinal surgeries.…”
Section: Evaluation Of Sensorial Blocksupporting
confidence: 53%
See 1 more Smart Citation
“…Only a few case reports have reported sensorial findings after lumbar ESPB. 8,17,23,25,28,30,[35][36][37][38][39][40][41][42][43][44][45][46][47] Spread of LA between T12 and S1 dermatomes were reported when 30-40 mL of LA was used, 28 with similar findings for the lower volume of 20 mL also reported. 30,38 Low volume injections have generally been utilized in back pain and spinal surgeries.…”
Section: Evaluation Of Sensorial Blocksupporting
confidence: 53%
“…8,29 The first use of lumbar ESPB and transmuscular QLB as the main anesthetic method was reported in a high-risk patient undergoing surgery for femur neck fracture. 37 In this case report, 40 mL LA and 20 mL of LA were used for ESBP and QLB, respectively. Surgery was completed successfully with minimal dose opioids and ketamine without the need for general anesthesia.…”
Section: Main Anesthetic Methodsmentioning
confidence: 98%
“…Other authors have shown its effectiveness as a second line therapy after the unsuccessful insertion of an epidural catheter [41] or its failure [49,51]. Additionally, it has been reported to successfully induce anesthesia in patients with a high risk of adverse effects from general anesthesia [30,31,85,86,99]. However, more randomized controlled trials are necessary to establish the best indications of ESP block as an analgesic technique, in chronic, acute, and postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the combined use of QLB and ESPB could increase the probability and range of the effect by devising the puncture site. A previous case report on the combined use of ESPB and QLB for hip surgery highlighted the importance of their mutual increase in effectiveness and complementing each other's missing aspects [15]. In the present cases, both patients weighed over 50 kg.…”
Section: Discussionmentioning
confidence: 49%